(untitled) (Journal of Scientific Research, 2013)
This investigation deals with the mortality rate of fish seeds (Labeo rohita) during traditional transportation system; to evaluate the effects of loading density with time scale under different water medium; temperature effect with relation to fry size and oxygen consumption; and the effect of saline water bath before transportation. Mortality rates were significantly increased with time scale and loading density under different water medium. Higher mortality was observed at 400 g L-1 loading density (river water 82%, pond water 70% and tubewell water 67.5%) than at 200 g L-1 and 300 g L-1 loading density after 24h. Oxygen consumption rate increased signi?cantly with increasing temperature and decreased significantly with increasing fry body weight. Therefore, mortality rate could decrease (22%) if fish fry are bathed in saline water before journey and tubewell water can be use as a medium for long distance transportation. Keywords: Mortality; Fish seeds; Oxygen consumption; Transportation. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.10572 J. Sci. Res. 5 (2), 383-392 (2013)